The New Testament : A Literary History - Theissen, Gerd (Book collections on Project MUSE., 2012)
"Gerd Theissen takes up the problem of the emergence of the New Testament canon out of the wide variety of early Christian literature. Drawing from Max Weber's discussion of the evolution of religious organizations, Theissen describes the development of early Christian literature as a series of phases in the life of the movement: the charismatic, the pseudepigraphic, the functional, and the canonical"--Publisher description